NAVIGATING GROWTH AND CHALLENGES IN JAPANESE STREET FOOD BUSINESS: A STRATEGIC SWOT AND IFE-EFE ANALYSIS OF KENKAYA - Permatasari, Dwi Novita Cahyaningtyas; I Gusti Ayu Ari Agustini,; Keno Kalyana Accariya Sentosa, (Journal of Innovation Research and Knowledge, 2025)
This study aims to analyze the growth dynamics, operational challenges, and development strategies of a Japanese street food business through a case study of Kenkaya. A descriptive qualitative method was employed, supported by SWOT analysis and the use of IFE and EFE matrix as analytical tools. The findings indicate that Kenkaya's business growth is driven by product quality that suits local tastes, affordable pricing, and an attractive menu variety. Digital promotions, including Instagram advertising, online ordering platforms, and customer loyalty programs, also play a significant role in attracting new customers. However, challenges such as a non-prime location, limited operating hours, and internal staff coordination issues remain significant obstacles. Kenkaya has implemented several strategies, including price discounts, loyalty cards, menu development, and quality control of ingredients. The SWOT analysis reveals strengths in product quality and competitive pricing, with opportunities arising from increased market interest in Japanese cuisine. Meanwhile, threats come from intense market competition and environmental conditions. The IFE score of 2.75 and EFE score of 2.85 place Kenkaya in Quadrant II of the SWOT matrix, suggesting a diversification strategy to leverage internal strengths in responding to external threats.